Synthesis and Photophysical Properties of Tumor-Targeted Water-Soluble BODIPY Photosensitizers for Photodynamic Therapy - Duy Khuong Mai; Byungman Kang; Temmy Pegarro Vales; Isabel Wen Badon; Sung Cho; Joomin Lee; Eunae Kim; Ho-Joong Kim (Molecules, 2020)
The synthesis of three water-soluble lactose-modified 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based photosensitizers with tumor-targeting capabilities is reported, including an investigation into their photodynamic therapeutic activity on three distinct cancer cell lines (human hepatoma Huh7, cervical cancer HeLa, and breast cancer MCF-7 cell lines). The halogenated BODIPY dyes exhibited a decreased fluorescence quantum yield compared to their non-halogenated counterpart, and facilitated the efficient generation of singlet oxygen species. The synthesized dyes exhibited low cytotoxicities in the dark and high photodynamic therapeutic capabilities against the treated cancer cell lines following irradiation at 530 nm. Moreover, the incorporation of lactose moieties led to an enhanced cellular uptake of the BODIPY dyes. Collectively, the results presented herein provide promising insights for the development of photodynamic therapeutic agents for cancer treatment.